ДИЈАЛОГОТ НА БЛАЖЕ КОНЕСКИ СО СРЕДНОВЕКОВНИОТ ФРЕСКОПИС (Philological Studies, 2019)
This article aims to present an analysis of the dialogue between Blaže Koneski (1921-1993) and medieval fresco painting, on two levels: 1) the role of fresco painting in Koneski’s poetry through an analysis of two of his emblematic poems (“Angelot na Sveta Sofija”; in English: Hagia Sophia’s Angel, and “Markoviot manastir”; in English: The Monastery of Saint Mark), and 2) the role of medieval fine arts in Blaže Koneski’s nonfiction through an analysis of several of his essays and lectures (“Svetlinata na nashite ochi”; in English: The Light of Our Eyes; “Sovpagjanja”; in English: Coincidences; and “Eden opit”; in English: An Experiment), in which the poet develops his views on literature and key points of his immanent poetics, by examining the relationship between literature and the fine arts.
Keywords: Blaže Koneski, fresco painting, medieval art, poetics, fine arts, coincidences